Val109Asp Polymorphism of the Omentin-1 Gene and Incidence of Knee Osteoarthritis in a Chinese Han Population: A Correlation Analysis - Chen R; Zhang Y; Xu H; Hu H; Chen M; Shuai Z (Dove Medical Press, 2021)
Ruofei Chen,1,* Yaqin Zhang,1,* Honggang Xu,2 Huaqing Hu,3 Mingwei Chen,4 Zongwen Shuai1 1Department of Rheumatology and Immunology, The First Affiliated Hospital of Anhui Medical University, Hefei, 230032, Anhui Province, People's Republic of China; 2Department of Sports Injury and Arthroscopic Surgery, The First Affiliated Hospital of Anhui Medical University, Hefei, 230032, Anhui Province, People's Republic of China; 3Health Management Center, The First Affiliated Hospital of Anhui Medical University, Hefei, 230032, Anhui Province, People's Republic of China; 4Department of Endocrinology, The First Affiliated Hospital of Anhui Medical University, Hefei, 230032, Anhui Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Mingwei Chen; Zongwen Shuai Email chmw1@163.com; amushuaizw@163.comObjective: To investigate the correlation of the Val109Asp polymorphism of the omentin-1 gene with the risk and severity of knee osteoarthritis (KOA) in a Chinese Han population.Methods: This study enrolled 383 patients with primary KOA and 460 healthy controls. The genotypes were determined by the detection of single nucleotide polymorphism. To explore the interaction between omentin-1 gene polymorphism and obesity and age, the body mass index (BMI) of 25 kg/m2 and the age of 55 years old were preset as the cut-off value of stratified analysis. Furthermore, enzyme-linked immunosorbent assay was used to determine the levels of omentin-1, interleukin (IL)-1β, IL-6 in peripheral blood and synovial fluid and the contents of IL-1β, IL-6, metalloproteinase (MMP)-13 and collagen (COL)-II in the supernatant of knee joint cartilage tissue.Results: The Val109Asp polymorphism of the omentin-1 gene showed no obvious correlation with KOA. Compared with Asp/Asp genotype carriers with BMI < 25 kg/m2 and age < 55 years old, Val109 allele carriers with BMI≥ 25 kg/m2 and age ≥ 55 years old had obviously increased risk of KOA (adjusted OR = 1.416, p = 0.042; adjusted OR = 1.735, p = 0.038, respectively). In the KOA group, only the omentin-1 levels were significantly lower in the plasma and synovial fluid of Ala/Ala genotype carriers than in those of Asp/Asp genotype carriers. Meanwhile, the proportion of patients with moderate-severe K-L Classification, the levels of IL-1β, IL-6 in synovial fluid and the expression levels of IL-1β, IL-6 and MMP-13 in cartilage tissue significantly increased (p < 0.05). By contrast, the expression level of COL-II in cartilage tissue significantly decreased (p < 0.05).Conclusions: The Val109Asp polymorphism of the omentin-1 gene may not be the primary pathogenic factor of KOA in Chinese. The Val/Val genotype can be regarded as a potential biomarker for the risk of KOA progression.Keywords: omentin-1, single nucleotide polymorphism, knee osteoarthritis, biomarker, Chinese, obesity